647 Research on the promoting children's knowledge of injury by chess games. (1st September 2016) - Ya-ming, Yang; xing, Gao; Meng-jing, Cui; Yu, Cheng; Yang, Li; Zhen, Li; Xujun, Zhang; Jun, Zhu
Abstract : Background: Injury is the most important factor in the threat to children's health and playing a game is children's favourite method of participation. We try to promote child injury prevention and improve mental health through the games. Methods: The chess game is designed and made by the National Centre for Disease Control and Prevention. Survey and intervention were conducted in 666 primary school students (Grade 3 to Grade 5) in Yixing City, Jiangsu Province from September 2014 to February 2015. Instrument was the Related questionnaire: Knowledge of injury prevention questionnaire and satisfaction questionnaire and the Mental health promoting chess: a 2–6 player game. Methods: Students played the game with the help of teacher, and then played the game by themselves. Two researches were conducted in the knowledge of injury before and after half a year. Finally, there was a satisfaction survey. Results: After the intervention, the children's injury prevention knowledge accuracy was higher than before. The difference was statistically significant (P < 0.05). Children who liked the chess were more than those who didn't. And children who wanted the chess were more than those who didn't if there were similar chess games. Girls prefer the chess than boys and there is no difference between grade groups. Conclusion: Chess games have a certain effect. It is welcomed and worthy of popularising.